2022
DOI: 10.1038/s41467-022-30654-4
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages disseminate pathogen associated molecular patterns through the direct extracellular release of the soluble content of their phagolysosomes

Abstract: Recognition of pathogen-or-damage-associated molecular patterns is critical to inflammation. However, most pathogen-or-damage-associated molecular patterns exist within intact microbes/cells and are typically part of non-diffusible, stable macromolecules that are not optimally immunostimulatory or available for immune detection. Partial digestion of microbes/cells following phagocytosis potentially generates new diffusible pathogen-or-damage-associated molecular patterns, however, our current understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…However, if the various molecules are not degraded into lysosomes, the mechanism cannot be properly defined as autophagic [40]. Our data are in agreement with Greene et al [53], who strongly suggested the extracellular release of toxin and bacterial molecules that were previously internalised. Therefore, the effect on neighbouring cells of a quantity of toxic materials released in the extracellular space was investigated.…”
Section: Lysosomal and Autophagic-like Vacuoles Involvement And Aberr...supporting
confidence: 87%
“…However, if the various molecules are not degraded into lysosomes, the mechanism cannot be properly defined as autophagic [40]. Our data are in agreement with Greene et al [53], who strongly suggested the extracellular release of toxin and bacterial molecules that were previously internalised. Therefore, the effect on neighbouring cells of a quantity of toxic materials released in the extracellular space was investigated.…”
Section: Lysosomal and Autophagic-like Vacuoles Involvement And Aberr...supporting
confidence: 87%
“…The uptake of the OVA-beads via phagocytosis results in the simultaneous loading of phagosomes with SRB. Unlike latex beads, the 3 μm silica beads used here are porous allowing for the entry of fluorescent molecules like SRB 43 ; as a result, the fluid-phase SRB is visible throughout the phagosome. Upon phagosomal rupture, fluid-phase SRB escapes into the cytosol, but covalently attached AF488 remains within the phagosome.…”
Section: Resultsmentioning
confidence: 99%
“…Having demonstrated ΔG β 4-induced hyperphagy in HL-60 cells, we next investigated whether this mechanism oper-ates in primary neutrophils and macrophages. By applying CRISPR-Cas9 targeting to the ER-HoxB8 immortalized murine neutrophil progenitor system(Hopke et al 2020; Greene et al 2022; Khoyratty et al 2021) (fig. S6a-b), we were able to generate primary neutrophils lacking β 4, along with controls expressing non-targeting guide (g)RNA.…”
Section: Resultsmentioning
confidence: 99%